Superstructure Design of PCI Girder Bridge (Case Study: Bridge Project in Padang Pariaman, West Sumatera) - Ahmad Yudi; Fadhilah Ramadhan; Kirtinanda P. Kirtinanda P.; Arif Rahman Hakim Sitepu (Universitas Islam Raden Rahmat, Malang, 2025)
This study was conducted in response to the damage of the Padang Pariaman Bridge, which had exceeded its service life, further worsened by a flood disaster in 2023 in Padang Pariaman, West Sumatra. The bridge redesign in this study adopts a PCI Girder type with a span of 35 meters. Load calculations refer to SNI 1725:2016, and structural analysis was carried out using MIDAS Civil software. The bridge design follows the AASHTO LRFD 2007 standards, covering the determination of the number and layout of tendons, loss of prestress analysis, concrete stress evaluation, deflection checks, and shear capacity design. The design results in this study serve as a redesign of the damaged bridge in Padang Pariaman, with adjustments made to the load combinations and response spectrum parameters specific to the region. The analysis results indicate the use of PCI Girder type H-170 with 64 strands divided into 4 tendons. A total prestress loss of 17.94% or 333.77 MPa occurred at midspan. The concrete section stresses remain below the limits specified in the standards, ensuring the section is safe from cracking. Additionally, deflection caused by the combination of vehicle and service loads remains within permissible limits. The bridge design also requires shear reinforcement with D13-200 specifications.